Determining competent jurisdiction in cross-border art disputes - B. Kryvolapov (Науковий вісник Ужгородського національного університету. Серія Право)
Throughout history, armed conflicts have often been accompanied by the unlawful export and looting of cultural property. The ongoing war in Ukraine is, regrettably, no exception. According to data from the Ministry of Culture and Strategic Communications of Ukraine and UNESCO, numerous cultural objects have been relocated to the territory of the aggressor state. As a result, the risks associated with the illicit circulation of cultural assets have significantly increased, highlighting the urgent need for effective legal mechanisms for their restitution. This article examines international and national rules governing jurisdiction in cases involving the return of cultural property, identifies existing legal conflicts, and evaluates optimal forums for adjudication. Special attention is given to EU judicial practice, particularly an analysis of the Brussels I bis Regulation, along with relevant laws in Switzerland, France, the United States, and other jurisdictions. The article concludes that the application of the forum rei sitae rule establishes a strong link between the cultural object and the court handling the dispute, which in turn facilitates more efficient legal proceedings, including the appointment of necessary expert assessments. The impact of classifying cultural objects as movable or immovable on jurisdictional outcomes is also explored. Using the example of the frescoes from the Casenoves Chapel, the article demonstrates how transnational movement can alter legal classification and jurisdiction. Furthermore, the article assesses the potential of alternative dispute resolution (ADR), particularly arbitration, in such cases. Examples from judicial and arbitration practice, including the landmark Altmann v. Austria case, illustrate that arbitration may offer a more expedient, specialized, and confidential means of resolving cultural property disputes. The article advocates for the further development of ADR in the field of cultural heritage protection and proposes amending Ukrainian legislation to clarify jurisdiction over disputes involving cultural assets.